2016
DOI: 10.1097/md.0000000000003976
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic [18F]fluorodeoxyglucose uptake measured by positron emission tomography/computed tomography in pulmonary hypertension

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…The switch from mitochondrial respiration to glycolysis, known as the "Warburg effect" when it happens under normoxic conditions, is well described for cancer cells and has also been confirmed to occur in pulmonary vascular cells isolated from PAH patients and animals (59,61). The pulmonary and RV L439 RAGE/IMPA1 INTERACTION IN PULMONARY HYPERTENSION glucose uptake measured by positron emission tomography (PET) was found to be elevated in PAH patients compared with healthy controls and correlated with the severity of PAH (11,49,62). In this study, we confirmed that the membrane translocation of two main glucose transporters, GLUT1 and GLUT4, was significantly increased in the lungs of animals with PAH, although the profile of this alteration for each transporter was different.…”
Section: Discussionmentioning
confidence: 94%
“…The switch from mitochondrial respiration to glycolysis, known as the "Warburg effect" when it happens under normoxic conditions, is well described for cancer cells and has also been confirmed to occur in pulmonary vascular cells isolated from PAH patients and animals (59,61). The pulmonary and RV L439 RAGE/IMPA1 INTERACTION IN PULMONARY HYPERTENSION glucose uptake measured by positron emission tomography (PET) was found to be elevated in PAH patients compared with healthy controls and correlated with the severity of PAH (11,49,62). In this study, we confirmed that the membrane translocation of two main glucose transporters, GLUT1 and GLUT4, was significantly increased in the lungs of animals with PAH, although the profile of this alteration for each transporter was different.…”
Section: Discussionmentioning
confidence: 94%
“…The glycolytic switch of metabolism in pulmonary vasculature is a well-accepted and characterized phenomenon in PAH. It was shown with a PET scanning of PAH patients that increased glycolysis in lungs and RV, similar to glycolytic changes seen in the tumors of cancer patients, correlates with the presence and severity of PAH [ 44 , 45 ]. However, there is still debate whether the glycolytic switch is secondary to electron transport chain dysfunction or is upregulated due to pathologic normoxic HIF1a signaling activation.…”
Section: Discussionmentioning
confidence: 99%
“…On previous studies, clinical risk factors for cardiovascular disease including hypertension, diabetes mellitus, and dyslipidemia have been known to be affect FDG uptake of the myocardium [37][38][39]. Therefore, in the present study, we also compared myocardial FDG uptake according to the history of hypertension, diabetes mellitus, and dyslipidemia.…”
Section: Discussionmentioning
confidence: 93%